ChemInform Abstract: Iron‐Catalyzed, Atom‐Economical, Chemo‐ and Regioselective Alkene Hydroboration with Pinacolborane. Issue 32 (18th July 2013) - Zhang, Lei; Peng, Dongjie; Leng, Xuebing; Huang, Zheng
Abstract The iron pincer complex (IPC) is found to be optimal as precatalyst in the transformation of various alkenes.